The Application of Coal Ash of Thermal Power Plant in Building Materials and Anti-salinity Foundation - Truc, Nguyen Ngoc; Van Hoan, Nguyen; Ngoc Tu, Tran; Trong Van, Nguyen (VNU Journal of Science: Earth and Environmental Sciences, 2022)
Abstract: Fly ash (FA) and coal bottom ash (CBA) of thermal power plants is industrial wastes but can be used for many different purposes. This paper focuses on the authors’ research on using CBA to successfully produce artificial sand to replace natural sand; using FA and CBA as aggregates for producing of non-fired brick, and applying of the important properties of CBA to prevent salinization of structures based on capillary test results combined with a specialized design method. The research and application of coal ash not only contribute to solving environmental problems and natural resources but also significantly contribute to promoting sustainable development and proactively responding to climate change.